2020
DOI: 10.1002/jbt.22623
|View full text |Cite
|
Sign up to set email alerts
|

Rutin ameliorates copper sulfate‐induced brain damage via antioxidative and anti‐inflammatory activities in rats

Abstract: Excessive exposure to Copper (Cu) may result in Cu toxicity and adversely affect health outcomes. We investigated the protective role of rutin on Cu‐induced brain damage. Experimental rats were treated as follows: group I: control; group II: Cu‐sulfate: 200 mg/kg; group III: Cu‐sulfate, and rutin 100 mg/kg; and group IV: rutin 100 mg/kg, for 7 weeks. Cu only treatment significantly decreased body weight gain, while rutin cotreatment reversed this decrease. Cu treatment increased malondialdehyde, nitric oxide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 90 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…This corroborates with previous reports on the antioxidative and anti‐inflammatory activities of strawberries (Erukainure, Salau, Oyenihi, et al., 2020; Giampieri et al., 2014; Rutledge et al., 2019). These activities can be attributed to the HPLC‐identified phenolics (Table 1) as they have been well documented for their potent antioxidative and anti‐inflammatory activities (Arowoogun et al., 2021; Salau et al., 2021; Salau et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…This corroborates with previous reports on the antioxidative and anti‐inflammatory activities of strawberries (Erukainure, Salau, Oyenihi, et al., 2020; Giampieri et al., 2014; Rutledge et al., 2019). These activities can be attributed to the HPLC‐identified phenolics (Table 1) as they have been well documented for their potent antioxidative and anti‐inflammatory activities (Arowoogun et al., 2021; Salau et al., 2021; Salau et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier study, psoralen isolated from Dystaenia takeshimana was reported to inhibit COX-2/5-LOX in mouse bone marrow-derived mast cells [33]. A few studies suggest that psoralen derivatives [34,35] and rutin [36][37][38] possess COX-2 inhibitory activity. For instance, 5-methoxy-8-(2-hydroxy-3-buthoxy-3-methylbutyloxy)-psoralen from Angelica dahurica was reported to inhibit induction of COX-2 in bone marrow-derived mast cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…The level of hepatic NO was assessed using Griess reagent, as previously described by Green et al (Arowoogun et al, 2021; Green et al, 1982). Briefly, the reaction mixture containing equal parts of sample and Griess reagent was incubated for 15 min, and the absorbance was taken at 540 nm.…”
Section: Methodsmentioning
confidence: 99%